Pengaruh Kampanye PR Gojek #PesanDariRumah terhadap Kesadaran Konsumen dalam Menaati Protokol Gojek J3K - Gandy Des Ardy; El Chris Natalia (Jurnal Komunikasi Pembangunan, 2022)
Various business sectors in Indonesia, which began operating again during the Covid-19 pandemic, must be balanced with innovations in health protocol standards as recommended by the government. One company that implements its health protocol innovation is Gojek with J3K: jaga kesehatan, kebersihan, dan keamanan (maintain health, cleanliness, and safety) which has 3 pillars, namely education, technology, and infrastructure. This study aims to determine the effect of Gojek's PR campaign #PesanDariRumah on consumer awareness in complying with Gojek’s J3K protocol. The #PesanDariRumah PR campaign in this study focused on all three #PesanDariRumah videos uploaded on Gojek Indonesia's official YouTube channel. This study has independent variables, namely PR campaigns with dimensions of message structure, message content, framing, language, and emotional appeal, and has a dependent variable, namely, consumer awareness with cognitive, affective, and conative dimensions. This study uses an explanatory quantitative research method with data collection techniques using online questionnaires to 96 respondents. The results showed that there was a positive effect with a correlation coefficient of 0.550, including a moderate level of relationship between Gojek's #PesanDariRumah PR campaign and consumer awareness in complying with Gojek’s J3K protocol.